An infant with glutaric aciduria type IIc diagnosed with a novel mutation - Isikay, Sedat; Yaman, Ayhan; Ceylaner, Serdar (TURKISH J PEDIATRICS, 2017)
Glutaric aciduria type II is a rare inborn error of metabolism. The clinical picture is highly variable with symptoms ranging from acute metabolic decompensations to chronic, mainly muscular problems or even asymptomatic cases. Herein we described a 7-month-old female patient presented with respiratory failure and diagnosed with glutaric aciduria type II via whole exome sequencing that exhibited one known and a novel mutation. Her blood and urine analyses were all normal. After the diagnosis, dramatic and sustained improvement on a low-fat, low-protein, and high-carbohydrate diet supplemented with oral riboflavin and carnitine was determined. In especially hypotonic patients with unknown etiologies, though the blood and urine analyses are normal, glutaric aciduria type II should also be kept in mind and genetic tests may be required for the diagnosis.
Keywords: glutaric aciduria; genetic test; child